Behavioral and psychological diagnosis for universities students after the corona pandemic closures - El Kailani, Ghazi; Fattah, Osama Abdel; Zureigat, Ayed A.; A’mir, Omar (International Journal of Public Health Science (IJPHS), 2023)
With the coronavirus's rapid spread, most countries have taken preventive measures to limit this spread. Therefore, this paper aims to explore university students' behavioral and psychological variables. To achieve this, the researchers used the descriptive survey approach to the 3,152 Jordanian university students (2,194 female and 1,058 male). We put the Generalized Anxiety Disorder screener GAD-7 and behavioral variables an electronic questionnaire using (Google Forms). To achieve the study's objectives, we used: means, standard deviations, frequencies, percentages, Pearson correlation coefficient, and Chi-square tests with a confidence level of 95% (p<0.05). The study results revealed that (66.34%) don’t do regular physical activity, and there were statistically significant differences between males and females in the practice of physical activities in favor of males. In addition, (64.47%) of the study sample spent (5-10) hours, and (26.6%) spent more than (10) hours on social networking sites. Also, (40.03%) of the study sample suffers from fat accumulation in the waist, pelvis, and thighs. There were also (60.32%) who suffered from sleep disorders. In addition, there are overlapping relationships between the study variables (anxiety level, sleep duration, time spent on social networks, physical activities, and body shape).